Biochar-Swine Manure Impact on Soil Nutrients and Carbon Under Controlled Leaching Experiment Using a Midwestern Mollisols - Banik, Chumki; Koziel, Jacek A.; De, Mriganka; Bonds, Darcy; Chen, Baitong; Singh, Asheesh; Licht, Mark A. (Frontiers in Environmental Science, 2021)
Biochar application to the soil can improve soil quality and nutrient leaching loss from swine manure adapted soils. Our working hypothesis was that the biochar-incubated with manure could be a better soil amendment than conventional manure application. The manure-biochar application to the soil would decrease nutrient leaching from manure and increase plant-available nutrients. The study objectives were to (1) assess the physicochemical properties of the manure-biochar mixture after lab incubation and (2) evaluate the impact of biochar-treated swine manure on soil total C, N, and other major and minor nutrients in comparison to conventional manure application to soil. Three biochars (i) neutral pH red-oak (RO), (ii) highly alkaline autothermal corn (Zea mays) stover (HAP), and (iii) mild acidic Fe-treated autothermal corn stover (HAPE) were incubated with swine manure for a month. The biochar-manure mixture was applied in triplicate to soil columns with an application rate determined by the P2O5-P content in manure or manure-biochar mixtures after the incubation. The ammonium (NH4+), nitrate (NO3-), and reactive P concentrations in soil column leachates were recorded for eight leaching events. Soil properties and plant-available nutrients were compared between treatments and control manure & soil. Manure-(HAP&HAPE) biochar treatments significantly increased soil organic matter (OM), and all biochar-manure mixture increased (numerically) soil total C, N, and improved soil bulk density. Concentrations of NH4+ and NO3- significantly increased in MHAPE column leachates during this 4-week study and the KCl-extractable NH4+ and NO3- in the soil at the end of the experiment. A significant reduction in soil Mehlich3 Cu was also observed for the manure-HAPE mixture compared with the manure control. The manure-red oak biochar significantly increased the soil Mn availability than other manure-biochar treatments or manure control. Overall, the manure-biochar incubation enabled biochar to stabilize the C and several nutrients from manure. The subsequent manure-biochar mixture application to soil improved soil quality and plant nutrient availability compared to conventional manure application. This proof-of-the-concept study suggests that biochars could be used to solve both environmental and agronomic challenges and further improve the sustainability of animal and crop production agriculture.